Implementation of the Each One Teach One and Student Debate Learning Model to Achieve Biology Learning Completeness and Critical Thinking at Senior High School - Yusal, Muh. Sri; Pratomo, Ryan Humardani Syam; Abdullah, Mohd Lokman; Nur, Sri Mukminati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
Learning models are activities carried out by teachers and students to achieve learning objectives effectively and efficiently. The study aims to examine the implementation of using the Each One Teach One and Student Debate learning models to achieve complete biology learning and critical thinking among senior high school students in Gowa Regency. The research is quantitative with a quasi-experimental research design; the 1st Experimental class was treated with the Each One Teach One model, and the second experimental class was treated through the Student Debate model. The research consists of the preparation stage, implementation of experiments, conclusions, and reporting results. At the end of each biology learning experiment, a post-test was conducted to determine the student's final ability. Each One Teach One and Student Debate learning model has a real effect on the learning outcomes of students in Science Class XI so that they reach the value of learning completeness. The results of hypothesis testing with a probability of 0.018 (<0.05) show that both learning models have a significant effect on learning completeness. The advantages of using this learning model are encouraging students to cooperate with their colleagues so as to create active learning, increasing analytical power, arousing learning motivation, establishing good communication, stimulating students to do their best individually and collectively, and arousing student creativity, and students' critical thinking skills achievement.